Evasión tributaria de los negocios asociados comerciales y su impacto en el desarrollo económico del cantón La Maná, Provincia de Cotopaxi. - Avilés Lucin, Ivonne Briggitte (2019)
The present research has as purpose to analyze the tributary evasion of the businesses associated and its impact in the economic development of La Maná to guide the taxpayers to comply with the tributary regulations and to know how they affect the economic growth. In La Maná, there are many commercial businesses, but not all of them know the field of taxation because they are not informed in an adequate manner. The SRI carries out controls, provides information and trains taxpayers to avoid evading taxes. The methodology used is quantitative based on statistical data, qualitative when interpreting the results, of a descriptive nature detailing in all the main components a reality, methodological when investigating the applied theoretical aspects of measurement, data collection and analysis, with the techniques of data collection. Data such as the interview and the survey through the questionnaire instruments that serve to evaluate the taxpayers and analyze the tributary evasion of the commercial businesses associated. This research is important because it shows the reality of the merchants about tributary compliance, a study based on tributary analysis with the purpose of examining and verifying the activities they perform, eliminating the shortcomings found and improving the control of the businesses through the use of a guide of tributary process. The economic impact is positive by involving the population in fulfilling their formal duties. The direct beneficiaries are the owners of the business partners who, when applying the proposal, know and analyze the advantages of complying with the current tributary laws, creating a sustainable tributary culture that benefits these organizations. The indirect beneficiaries are the population of La Maná with the values of the collection of taxes benefit from the realization of works, on the other hand, the “SRI” to increase their income and the Municipality of La Maná.